The effect of hyperglycemia on the regulation of sodium homeostasis in experimental diabetes mellitus - Grytsiuk, M. I. (Journal of Education, Health and Sport, 2017)
The studies were carried out on the 11th, 21st and 31st days after the administration of streptozotocin. The results of the experiments showed that on the 11th and 21st days the changes in the amount of transport of sodium ions in the proximal tubules and some other changes in the parameters of kidney activity were adaptive, whereas on the 31st day, it is possible to assume the presence of damage to the kidney tissue.